Collisions at the crossroads how place and mobility make race - Carpio, Genevieve (American crossroads, 2019)
"Collisions at the Crossroads examines mobility--the means by which we experience, manage, and give meaning to everyday channels of movement--as an agent in the production of racial difference. It demonstrates the ways forces as different as historical societies, Indian boarding schools, bicycle ordinances, alien land laws, immigration policy, traffic checkpoints, fair housing, incarceration, and Route 66 heritage construct racial hierarchies by allowing some people to move freely while placing limits on the mobility of others. Further, it examines the ways people of color have negotiated their place within these meaning systems through claiming the right to mobility or, in other instances, the right to stay put. This work focuses on the development of the Inland Empire, an understudied region located east of metropolitan Los Angeles, over the course of the 20th century"--Provided by publisher